GAMBARAN TINGKAT PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK USIA SEKOLAH DI WILAYAH KELURAHAN RAWABUAYA - Abu Bakar (Jurnal Nurse, 2022)
Knowledge of dental and oral hygiene is very important for the formation of actions in maintaining dental and oral hygiene. Dental and oral hygiene is done to prevent dental and oral diseases. Maintaining dental and oral hygiene at school age is one way to improve health at an early age. This study aims to determine the level of knowledge of children about dental and oral health in class V and VI students in the Rawabuaya Indah Urban Village, West Jakarta. The research method used is a simple descriptive method. The sample size in this study was 124 people who were recruited using a total sampling technique. The instrument used was a knowledge questionnaire about dental and oral health. Data analysis technique with univariate analysis. The results showed that the level of children's knowledge about dental and oral health in grades V and VI in the Rawabuaya Urban Village area, West Jakarta, namely 85 students (68.5%) in the high category, 25 students (20.2%) in the medium category, and 14 students. (11.3%) in the low category.